P47 CLEVER-1 mediates T regulatory cell recruitment via hepatic sinusoidal endothelium by transcellular migration. (16th November 2010) - Shetty, S; Weston, C; Oo, Y; Westerlund, N; Stamataki, Z; Youster, J; Hubscher, S; Salmi, M; Jalkanen, S; Lalor, P; Adams, D H
Abstract : Introduction: Lymphocytes are recruited via the unique hepatic sinusoidal channels during chronic inflammatory liver diseases. This low shear vascular bed is lined by hepatic sinusoidal endothelium (HSEC) which lacks certain conventional adhesion molecules leading us to look for novel receptors involved in lymphocytes recruitment. HSEC express several receptors found on lymphatic endothelium including the scavenger receptor CLEVER-1 which has been implicated in lymphocyte migration to lymph nodes. Aim: We now show that CLEVER-1 is upregulated on human hepatic sinusoidal endothelium where it is involved in lymphocyte transendothelial migration. Method: We studied the expression of CLEVER-1 in normal and diseased human liver tissue and on isolated human sinusoidal endothelial cells. We used isolated HSEC in flow adhesion assays to study the functional role of CLEVER-1 in lymphocyte subset recruitment. Immunofluorescent staining and confocal microscopy were used to characterise the transmigration of lymphocytes across HSEC under conditions of flow. Results: CLEVER-1 was expressed at high levels within the sinusoids of chronically inflamed livers and hepatocellular carcinomas as well as at other sites of lymphocyte recruitment including neo-vessels and portal associated lymphoid tissue. Flow-based adhesion assays using human HSEC demonstrated that CLEVER-1 mediates transmigration of CD4 but not CD8T cells with strong preferential activity for FoxP3+regulatory T cells. Confocal microscopy demonstrated that a large proportion of CD4 Treg transmigrated via the transcellular route through CLEVER-1 lined channels within the endothelial cell. Conclusion: This is the first report to implicate a specific adhesion molecule in the recruitment of T regulatory cells to tissue. CLEVER-1 appears to mediate the transcellular migration of Tregs through hepatic sinsuoids and is an organ specific target for therapy aimed at modulating Treg recruitment to the liver.